2014
DOI: 10.1140/epjc/s10052-014-3186-7
|View full text |Cite
|
Sign up to set email alerts
|

A note on “Electron self-energy in logarithmic electrodynamics” by P. Gaete and J. Helayël-Neto

Abstract: We propose an identification of the free parameter in the model of nonlinear electrodynamics proposed in Gaete and Helayël-Neto (Eur Phys J C 74:2816, 2014) by equating the second term in the power expansion of its Lagrangian with that in the expansion of the Heiseberg-Euler Lagrangian. The resulting value of the field-energy of a pointlike charge makes 0.988 of the electron mass, if the charge is that of the electron.Recently Gaete and Helayël-Neto [1] proposed a nonlinear Lagrangian for what they called th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…From Eqs. (6), (8) we observe that the relation D · H = ε 2 E · B holds. As a result, D · H = E · B, and according to [5] (see also [35]) we make a conclusion that the dual symmetry is violated in our model.…”
Section: Nonlinear Arcsin-electrodynamicsmentioning
confidence: 57%
See 1 more Smart Citation
“…From Eqs. (6), (8) we observe that the relation D · H = ε 2 E · B holds. As a result, D · H = E · B, and according to [5] (see also [35]) we make a conclusion that the dual symmetry is violated in our model.…”
Section: Nonlinear Arcsin-electrodynamicsmentioning
confidence: 57%
“…It was also shown that Maxwell and BI theories bear both dual invariance [5,6] (see also [7]). Some models of NED were proposed where there is no singularity of the electric field at the origin of charged particles and the total electromagnetic energy is finite [8][9][10][11]. The finiteness of the electric energy of charged particles makes it passible to treat the mass of the electron as a pure electromagnetic energy.…”
Section: Introductionmentioning
confidence: 99%
“…Making use of Eqs. (21) and (40) and introducing unitless parameter y = (2/(βq 2 m )) 1/4 r we obtain the metric function…”
Section: Magnetic Bhmentioning
confidence: 99%
“…The analysis of the metric function can be performed with the help of the exact mass function (25), which is valid for any r = 0, and the definition of A(r) given in Eq. (21). We will make this analysis in Sec.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Another attractive feature of some NLED is that there is an upper limit on the electric field at the origin of point-like particles and the selfenergy of charges is finite. Thus, in NLED models [9][10][11][12] there are no problems of singularity and the infinite self-energy of charged particles. In quantum electrodynamics nonlinear terms appear due to loop corrections.…”
Section: Introductionmentioning
confidence: 99%